2011
DOI: 10.1093/socrel/srr017
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Religion and Helping Others: The Role of Values, Ideas, and Language

Abstract: This study used life narrative interview data from the Midlife in the United States (MIDUS) study to examine how religious values, ideas, and language motivate prosocial behaviors. Open coding of 88 in-depth interviews revealed six themes: defining morality in religious terms, considering religion an important aspect of one's identity, feeling that one's life involves carrying out God's mission, making an increased commitment to religion over time, drawing an explicit connection between religion and helping ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 27 publications
0
69
0
5
Order By: Relevance
“…A possible contributory factor to this result is the historical internationalness of both Buddhism and Christianity -the two most prevalent religions in Hong Kong -alongside the emphasis on pro-social values such as altruism and responsibility for the common good found in both religions. In many respects, previous empirical studies have found that involvement in a religious organization instils generativity and positive attitudes towards volunteering and helping behaviour in people; and predicts a higher level of civic engagement and community participation (Bekkers & Schuyt, 2008;Einolf, 2011;Perks & Haan, 2011;Son & Wilson, 2011;Tao & Yeh, 2007;Webber, 2012). In terms of age, the results showed that compared to the students aged 19 or under, the students over the age of 20 had a more positive view towards globalization's benefits in relation to "personal consumption and choice" (t ¼ 2 2.59, p , .05).…”
Section: Asia Pacific Journal Of Education 115mentioning
confidence: 99%
“…A possible contributory factor to this result is the historical internationalness of both Buddhism and Christianity -the two most prevalent religions in Hong Kong -alongside the emphasis on pro-social values such as altruism and responsibility for the common good found in both religions. In many respects, previous empirical studies have found that involvement in a religious organization instils generativity and positive attitudes towards volunteering and helping behaviour in people; and predicts a higher level of civic engagement and community participation (Bekkers & Schuyt, 2008;Einolf, 2011;Perks & Haan, 2011;Son & Wilson, 2011;Tao & Yeh, 2007;Webber, 2012). In terms of age, the results showed that compared to the students aged 19 or under, the students over the age of 20 had a more positive view towards globalization's benefits in relation to "personal consumption and choice" (t ¼ 2 2.59, p , .05).…”
Section: Asia Pacific Journal Of Education 115mentioning
confidence: 99%
“…Indeed, we do not know of a single study that has used a representative sample of Americans to examine the influence of personal religious beliefs on willingness to help government officials address terrorism or crime. However, much research has examined the influence of religion more generally on volunteering and helping behaviors (Park and Smith, 2000;Regnerus et al, 1998;Perry et al, 2008;Einolf, 2011). Overall, this work shows that more religious people are more likely to help others both within and outside their congregations.…”
Section: Religiosity and Responses To Terrorist Threatsmentioning
confidence: 78%
“…The common socio-demographic factors that have been found to have an impact are gender, ethnicity, age, income, and educational background (Schlegelmilch et al 1997;Wilson 2012;Sargeant 1999;Einolf 2011;Gittell and Tebaldi 2006;Wiepking and Bekkers 2012). Social contexts are social factors that have an impact on attitudes towards NPOs, such as the feeling of belonging to a community (Reed and Selbee 2001;Wilson 2012), prior engagement in and social ties to NPO activities (Sokolowski 1996) or, more generally, greater levels of social capital (Brown and Ferris 2007;Wang and Graddy 2008), as well as social incentives such as social conformity and social exchange (Bekkers 2010;Green and Webb 1997).…”
Section: Micro-level Traits and Motivations That Shape Attitudes Towamentioning
confidence: 99%